(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Commercial banks play a crucial role not only as the primary financial institutions within the national economy but also in the global financial market. Their operations facilitate capital mobilization, allocation of financial resources, and promotion of economic development. The investment attractiveness of banks determines their competitiveness, financial stability, and potential for long-term growth. From this perspective, enhancing investment attractiveness is considered a strategic objective of banking operations